Fractional-Stochastic Solutions for the Generalized (2+1)-Dimensional Nonlinear Conformable Fractional Schrödinger System Forced by Multiplicative Brownian Motion - Sahar Albosaily; Wael W. Mohammed; Ekram E. Ali; R. Sidaoui; E. S. Aly; M. El-Morshedy (Journal of Function Spaces)
In this paper, the (2+1)-dimensional nonlinear conformable fractional stochastic Schrödinger system (NCFSSS) generated by the multiplicative Brownian motion is treated. To get new rational, trigonometric, hyperbolic, and elliptic stochastic solutions, we use two different methods: the sine-cosine and the Jacobi elliptic function methods. Moreover, we use the MATLAB tools to plot our figures to introduce a variety of 2D and 3D graphs to highlight the effect of the multiplicative noise on the exact solutions of the NCFSSS. Finally, we illustrate that the multiplicative Brownian motion stabilizes the solutions of NCFSSS a round zero.